Retrieval and Replacement of Fractured Zirconia Abutment - Wali, Othman (Journal of Orofacial Research, 2014)
Zirconia was newly introduced to implant dentistry as an abutment to enhance esthetic result. However, careful handling, is recommended to avoid failures. Mechanical complications, such as loosening or damaging of the prosthetic components of an osseointegrated implant, may occur. Fracture of zirconiaabutment is not uncommon. This report describes a clinical situation involving a patient, who presented with a fractured Zirconia abutment. Upon further examination, it was determined that the abutment was fractured at the base. There was limited access and visibility in this situation since the implantwas a bone-level implant. The procedure used for the removal of the fractured zirconia abutment is described in detail in this clinical report.